2022
DOI: 10.3174/ajnr.a7432
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Effectiveness of Interventions That Target the Reporting, Communication, or Clinical Interpretation of Lumbar Imaging Findings: A Systematic Review

Abstract: BACKGROUND: Patients and clinicians may misinterpret the clinical importance of imaging findings in patients with low back pain, leading to potential harm related to overdiagnosis. PURPOSE: Our aims were to qualitatively summarize the characteristics of tested interventions that target the reporting, communication, or clinical interpretation of lumbar imaging findings and determine whether interventions are effective in improving low back pain-related health outcomes, health care use, or health care costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Terms that are commonly provided in diagnostic imaging reports such as ‘disc degeneration’ are poorly understood by the general population [ 39 ], may increase patients perceived need for imaging [ 40 ], and may not, therefore, be inherently reassuring. Strategies have been investigated to try and reduce unintended harm associated with the reporting of radiographic findings [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Terms that are commonly provided in diagnostic imaging reports such as ‘disc degeneration’ are poorly understood by the general population [ 39 ], may increase patients perceived need for imaging [ 40 ], and may not, therefore, be inherently reassuring. Strategies have been investigated to try and reduce unintended harm associated with the reporting of radiographic findings [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to prevent harmful MSK image reporting behaviours, studies have evaluated the withholding of imaging reports,15 reassurance about the lack of serious pathology17 and the insertion of information about the prevalence of findings in the pain free population 18. A recent systematic review, however, found little evidence of effectiveness for any of the interventions 19. While these interventions attempted to change clinician-reporting behaviours, they did not outline a thorough intervention design process informed by theory.…”
Section: Introductionmentioning
confidence: 99%
“… 18 A recent systematic review, however, found little evidence of effectiveness for any of the interventions. 19 While these interventions attempted to change clinician-reporting behaviours, they did not outline a thorough intervention design process informed by theory. The National Institute for Health and Care Research and Medical Research Council 20 recommend using behavioural science in the development of interventions to improve effectiveness and the lack of such a process in these studies may have contributed to their lack of effectiveness.…”
Section: Introductionmentioning
confidence: 99%